2013
DOI: 10.1007/s12070-013-0644-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Foreign Bodies in Aerodigestive Tract in Vindhya Region: Our Experience

Abstract: Foreign bodies in aerodigestive tract are frequent occurrence and may lead to life threatening situation due to obstruction caused in respiratory passages. To present foreign body ingestion cases observed in a 5-year period at the S.S. Medical College and G.M. Hospital, Rewa (MP). The present study is a retrospective analysis including 108 patients of foreign bodies of aerodigestive tract of Vindhya region who presented to the S.S. Medical College and G.M. Hospital, Rewa from January 2008 to August 2012. About… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 12 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…11,13,14,[16][17][18] The majority of objects retrieved were coins, in accordance with various other investigations. 5,[11][12][13][16][17][18]23 A handful of studies conducted outside the United States found other, culturally relevant objects to be most commonly ingested, such as pins, 3 blue beads attached to a safety pin (a Turkish cultural good luck charm), turban pins, 20 and fish bones. 14 A minority of patients (2%) in this investigation were asymptomatic at the time of presentation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…11,13,14,[16][17][18] The majority of objects retrieved were coins, in accordance with various other investigations. 5,[11][12][13][16][17][18]23 A handful of studies conducted outside the United States found other, culturally relevant objects to be most commonly ingested, such as pins, 3 blue beads attached to a safety pin (a Turkish cultural good luck charm), turban pins, 20 and fish bones. 14 A minority of patients (2%) in this investigation were asymptomatic at the time of presentation.…”
Section: Discussionsupporting
confidence: 87%
“…The gender ratio of children with foreign body ingestion in the current study is similar to previously reported data, namely, a slight male predominance. [3][4][5][11][12][13][16][17][18][19][20] The mean age of 4.7 years in this study is slightly older when compared to many other retrospective chart reviews (2.3-4.3 years). [3][4][5]11,20 Most children presented within 48 hours of ingestion, analogous to other studies in the literature.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It may impaction in tonsil, base of tongue, hypopharynx, piriform fossae and oesophagus or sometimes in the larynx or lower down in the respiratory tract that may be life threatening and need immediate removal because it can lead medical or surgical emergencies which are often challenging for an otorhinolaryngologist. [1][2][3][4][5] Accidental ingestion of foreign bodies and their impaction is more common in children than adult. In children exploring their environment with their mouth, uncoordinated swallowing, absence of molars for proper chewing are at risk for the ingestion and aspiration of small edible object.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction with Magill forceps and direct laryngoscope have been reported as an immediately procedure that should be performed to a foreign body in the pharynx and proximal esophagus. 3,5,6,14 Various studies have been reported the extraction of foreign bodies in pharynx with tracheostomy procedure to reduce the risk of morbidity and mortality. Preparation for performed tracheostomy in cases with a foreign body or virtually lodged the airway should be done to save the airway.…”
Section: Introductionmentioning
confidence: 99%